In mathematics, a set of simultaneous equations, also known as a system of equations or an equation system, is a finite set of equations for which common solutions are sought.

An equation system is usually classified in the same manner as single equations, such as:

An equation system is usually classified in the same manner as single equations, such as:

System of linear equations,

System of nonlinear equations,

System of bilinear equations etc.

System of nonlinear equations,

System of bilinear equations etc.

There are many methods of solving simultaneous equations such as: Substitution method, Elimination method etc. I will use one example here to solve by substitution so as to make you understand more on how to solve Tricky Fruits Maths Questions

Since there are always set in this format and others which many people usually fail it( Facebook Fan page).

Since there are always set in this format and others which many people usually fail it( Facebook Fan page).

The method of solving "by substitution" works by solving one of the equations (you choose which one) for one of the variables (you choose which one), and then plugging this back into the other equation, "substituting" for the chosen variable and solving for the other. Then you back-solve for the first variable.

Here is how it works.

Here is how it works.

Solve the following system by substitution.

2x – 3y = –2

4x + y = 24.

The idea here is to solve one of the equations for one of the variables, and plug this into the other equation. It does not matter which equation or which variable you pick. There is no right or wrong choice; the answer will be the same, regardless. But some choices may be better than others.

For instance, in this case, can you see that it would probably be simplest to solve the second equation for "y =", since there is already a y floating around loose in the middle there? I could solve the first equation for either variable, but I'd get fractions, and solving the second equation for x would also give me fractions. It wouldn't be "wrong" to make a different choice, but it would probably be more difficult.

Being lazy, I'll solve the second equation for y:

4x + y = 24

y = –4x + 24

Now I'll plug this in ("substitute it") for "y" in the first equation, and solve for x:

2x – 3(–4x + 24) = –2

2x + 12x – 72 = –2

14x = 70

4x + y = 24.

The idea here is to solve one of the equations for one of the variables, and plug this into the other equation. It does not matter which equation or which variable you pick. There is no right or wrong choice; the answer will be the same, regardless. But some choices may be better than others.

For instance, in this case, can you see that it would probably be simplest to solve the second equation for "y =", since there is already a y floating around loose in the middle there? I could solve the first equation for either variable, but I'd get fractions, and solving the second equation for x would also give me fractions. It wouldn't be "wrong" to make a different choice, but it would probably be more difficult.

Being lazy, I'll solve the second equation for y:

4x + y = 24

y = –4x + 24

Now I'll plug this in ("substitute it") for "y" in the first equation, and solve for x:

2x – 3(–4x + 24) = –2

2x + 12x – 72 = –2

14x = 70

x = 70 ÷ 14

x = 5.

Now I can plug this x-value back into either equation, and solve for y. But since I already have an expression for "y =", it will be simplest to just plug into this:

y = –4(5) + 24 = –20 + 24 = 4

Then the solution is (x, y) = (5, 4).

Warning: If I had substituted my "–4x+ 24" expression into the same equation as I'd used to solve for "y =", I would have gotten a true, but useless, statement:

4x + (–4x + 24) = 24

4x – 4x + 24 = 24

24 = 24 Twenty-four does equal twenty-four, but who cares? So when using substitution, make sure you substitute into the other equation, or you'll just be wasting your time

Concluding, solving this type of linear equations is indirectly asking you to look for meeting point between the two lines.Now I can plug this x-value back into either equation, and solve for y. But since I already have an expression for "y =", it will be simplest to just plug into this:

y = –4(5) + 24 = –20 + 24 = 4

Then the solution is (x, y) = (5, 4).

Warning: If I had substituted my "–4x+ 24" expression into the same equation as I'd used to solve for "y =", I would have gotten a true, but useless, statement:

4x + (–4x + 24) = 24

4x – 4x + 24 = 24

24 = 24 Twenty-four does equal twenty-four, but who cares? So when using substitution, make sure you substitute into the other equation, or you'll just be wasting your time